Efectos de fracciones lipídicas de Lepidium meyenii Walpers «maca», en el aparato reproductor de ratones - Marín, Manuel (2003)
The purpose of the present investigation has been to observe the effect of the lipidic fractions of Leoidium meyenii Walpers, «maca» on the reproductive organs of female mice, following the method adapted by S. Garg et al (1998) The yellow maca from central andean rcgion (Puna, Junín) was used. Initially we obtained the hexanic and ethanolic éxtracts by means of saponification of the first one, fatty acids and total sterols were separated. Lipidic fractions, which were oraily administered to four groups of female mice in dosis of 200 and 100 mg/kg respectively for a period of 16 days, maintaining the control group. For the histological observation the animals were sacrificed and their avaries were fixed previous to its inclusion in paraffin.The results demostrated a significant stimulative effect on the folliclegenesis with the total sterols fraction on the ovaries of the evaluated animals, inducing formation of secondary follicles after 16 days of the treatment in the doce of 100 mg /kg on the contrary, the hexanic extract and the total fatty acids fraction, in 200 and 100 mg/ kg respectively, they demostrated depressor effect on the reproductive system, diminishing the weight and the diameter of the ovaries, as well as the number of secondary follicles, on the 8th and 16th days of treatment. The dose levels used for the hexánic extract and the total fatty acids fraction showed an apposed effect to that of the total sterols fraction. The ethanolic extract, from the residue of the hexánic maceration, did not reveal any change at the leve1 of the reproductive system of the studied animals. We conclude that in experimental conditions, the lipidic fractions offer different effects on the reproductive organs of the evaluated animals, which it seems is dose depending effect.